Knowledge of and Attitudes toward Child Trafficking in Wolaita Sodo, Southern Ethiopia: Insights from the Origin Community (African Human Mobility Review, 2025)
Child trafficking is a serious violation of children’s rights under international law, particularly the United Nations Convention on the Rights of the Child (UNCRC). Research on this issue in Ethiopia is limited, with few studies assessing public awareness and attitudes. This study aims to examine the knowledge and attitudes of residents in Wolaita Sodo town regarding in-country child trafficking using a mixed-methods approach with 448 participants. The research team collected data through structured questionnaires, focus group discussions, and in-depth interviews. For data analysis, the researchers used SPSS 26.0 software, applied descriptive and inferential statistical analysis wherever applicable, and analyzed qualitative data thematically. The findings revealed that the majority of participants (55%) lacked adequate knowledge about child trafficking, with the qualitative results supporting this finding. In contrast, 55.9% of participants exhibited positive attitudes toward child trafficking.A significant correlation was found between knowledge levels and attitudes, with education and personal experiences playing a critical role. Multivariate analysis revealed that individuals with a first-degree education or higher were 3.25 times (1.21-8.81, p